Synergetic Analgesic Effect of the Combination of Arnica and Hydroxyethyl Salicylate in Ethanolic Solution Following Cutaneous Application by Transcutaneous Electrostimulation - Kucera, Miroslav; Horácek, Ondrej; Kálal, Jan; Kolár, Pavel; Korbelar, Peter; Polesná, Zora (Arzneimittelforschung, 2003)
A combination of the active agents arnica and hydroxyethyl salicylate (HES) in ethanolic solution (Sportino® Acute Spray) is cutaneously applied for the treatment of sports injuries and diseases of the locomotor apparatus. The aim was to examine the efficacy and synergism of the single substances and the combination with regard to the analgesic effect after cutaneous application as well as to validate the method of transcutaneous electronic stimulation as a method of measuring the analgesic effect. In the present article, the method of transcutaneous electrostimulation was used in a randomized, controlled, single-blind trial on healthy volunteers to provide objective evidence that the combination of active agents displays a significantly greater analgesic effect than the individual active agents. Thus there is synergy between the active agents arnica and hydroxyethyl salicylate in the combination preparation. In addition, the effect of the vehicle ethanol and the reference substance water could be determined within the framework of these comparative experiments and the difference between the combination preparation and the individual substances arnica and HES could be shown. The method of transcutaneous electrostimulation used for the objective measurement of the analgesic effect was validated.
Keywords: Analgesics; Arnica; Hydroxyethyl salicylate; Sportino® Acute Spray; Transcutaneous electrostimulation